2015
DOI: 10.1007/s12195-015-0423-6
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Ethylene Glycol) Hydrogel Scaffolds Containing Cell-Adhesive and Protease-Sensitive Peptides Support Microvessel Formation by Endothelial Progenitor Cells

Abstract: The development of stable, functional microvessels remains an important obstacle to overcome for tissue engineered organs and treatment of ischemia. Endothelial progenitor cells (EPCs) are a promising cell source for vascular tissue engineering as they are readily obtainable and carry the potential to differentiate towards all endothelial phenotypes. The aim of this study was to investigate the ability of human umbilical cord blood-derived EPCs to form vessel-like structures within a tissue engineering scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 65 publications
0
46
0
Order By: Relevance
“…Although functionalized PEG hydrogels have been used for epithelial (31), endothelial (32), connective tissue (33), and stromal cells (34), co-cultures of epithelial and stromal cells require tuning matrix properties to meet the needs of both cell types (35). Hence, we first established an endometrial stromal and epithelial co-culture in functionalized PEG gels as a model of a complex, multicellular, 3D system that can be interrogated through SrtA-mediated gel dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Although functionalized PEG hydrogels have been used for epithelial (31), endothelial (32), connective tissue (33), and stromal cells (34), co-cultures of epithelial and stromal cells require tuning matrix properties to meet the needs of both cell types (35). Hence, we first established an endometrial stromal and epithelial co-culture in functionalized PEG gels as a model of a complex, multicellular, 3D system that can be interrogated through SrtA-mediated gel dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Our model also provides a tool to investigate matrix remodeling in organotypic capillary morphogenesis with specific EC and stromal cell combinations. Finally, the unique matrix‐centric perspective of these studies provides strong evidence to justify the preferential selection of MMP‐degradable peptide crosslinkers in synthetic hydrogels used to study vascular morphogenesis and promote vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…[26, 27] Similarly, PEO as a synthetic polyether (also known as poly(ethylene glycol) (PEG) at small molecular weights), is prevalently used as hydrogel scaffolds for biomedical applications owing to its biocompatibility, inertness, and readily available molecular modifications. [28] Studies have shown that the addition of PEG increases the strength of hydrogen bonding between gelatin chains and results in phase separation of the gelatin/PEG aqueous solutions at both above and below the gelation temperature of gelatin. [29, 30] …”
mentioning
confidence: 99%